ORGANIZATION OF DISTANCE EDUCATION OF CHILDREN WITH DISABILITIES UNDER THE CONDITIONS OF MARTIAL LAW - Lisovets , Oleg; Uvarova, Valentyna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article deals with the issue of ensuring the right to education of children with disabilities under martial law. The state and problems of the organization of distance learning in the conditions of inclusive education during the period of martial law are analyzed.